NEGOTIATION STRATEGIES USED BY THE TEACHER IN TEACHING SPEAKING - Rizki Wahyudi (Journal of English Education Program (JEEP), 2018)
This study reports negotiation strategies used by the teacher in teaching speaking, particularly at a senior high school class. Meaning negotiation is a process that the speakers go through to reach a clear understanding of each other. In this regard, two questions are addressed: (1) How is negotiation strategies implemented by the teacher in teaching speaking ? (2) What type of  negotiation strategies is most preferred by students? To get the data the researcher administered interview and conducted classroom observation to one teacher and 34 students at class IPA 1 in tenth grade of SMAN 1 Ciamis.A transcript of the teacher and students interaction was taken as the main source of data. the researcher analyzed the data by using Pica and Doughty theory (1987) namely; comprehension check, confirmation check, clarification request. The result show that there are three categories in negotiation strategies used by the teacher in teaching speaking . Namely requests (38.09%), comprehension check (33.33%), and the last confirmation check (28.58%). The results  indicates that the  conversational adjustment like confirmation checks, comprehension checks and clarification requests implemented by the teacher in teaching speaking. Among these categories, clarification requests were the most frequently used  strategies in teaching speaking.